Social Emergence in International Relations Institutional Dynamics in East Asia - Wagner, Maren; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book presents a conceptualization of social emergence in international relations as a novel angle to analyse institutional dynamics in East Asia, introducing the concept of emergence from a critical realist perspective. The author examines East Asia's characteristic mesh work of regional institutions that affect integrative processes and regional policies, exploring how such institutions emerge and acquire their own nature and why this pattern persists over time, an unresolved and contested subject in the field of International Relations. This book suggests that regional institutions are emergent entities of the international system that arise as forms of self-organization by states to achieve certain emergent properties and powers. The author's approach sheds light on the particular emergent properties and powers of regional institutions and identifies discourse as a key mechanism of social emergence. Besides engaging in relevant questions of the philosophy of science and its methodological implications for studying social emergence in world politics, the book also analyses the concrete case of two East Asian regional institutions: ASEAN Plus Three and the East Asia Summit. This book will engage scholars and postgraduate students of Asian Studies and International Relations. Maren Wagner is a Research Fellow at the German Institute of Global and Area Studies (GIGA) and is Coordinator of GIGA's Doctoral Programme. She completed her PhD in political science at the University of Hamburg, Germany, and worked as an Assistant Lecturer at the University of Kiel, Germany.
Part I -- 1. The issue of institutional emergence in East Asia: an introduction -- 2. A critical realist approach to the study of world politics -- 3. Emergence and complexity in the international system: developing a social ontology of international relations -- 4. Emergence and the complexity of social practices: the role of discourse in social emergence -- Part II -- 5. The case of institutional emergence in East Asia: analyzing regional institutions as emergent entities - a critical realist informed critical discourse analysis -- 6. Examining the role of discourse in institutional emergence in East Asia using the example of ASEAN Plus Three and the East Asia Summit -- 7. The relevance of emergence in world politics: conclusion and outlook.
Keywords: Asia-Politics and government